Financing to Deposit Ratio dan Non-Performing Financing: Peran Islamic Corporate Governance - Rosidi, Rosidi; Putri, Intan Lifinda Ayuning; Nugraha, Rizky Aditya (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This research aims to analyze the role of Islamic Corporate Governance (ICG) in mediating and moderating the influence of financing to deposit ratio (FDR) on the level of non-performing financing (NPF) of Islamic banks in Indonesia. Method: This research uses panel data from 7 Islamic banks in Indonesia during the 2016-2021 period. Samples were taken using judgment sampling techniques. The analytical method used is panel regression with a fixed effect model and uses SPSS software. Results: The research results show that there is no evidence that the financing to deposit ratio has a negative and significant effect on ICG. On the other hand, ICG has a negative and significant effect on NPF, and the financing to deposit ratio also does not have a positive and significant effect on NPF. Apart from that, the research results also show that ICG is not proven to mediate the negative influence of financing to deposit ratio on NPF. On the other hand, the moderating effect of ICG on the relationship between FDR and NPF is proven to have an impact. FDR has a significant influence on NPF. Implications: The implication of this study is that Islamic banks in Indonesia need to improve ICG practices as an internal control mechanism to reduce the risk of non-performing financing and improve financial performance. Novelty: This research uses two models of the role of Islamic Corporate Governance (ICG) in mediating and moderating the influence of the Financing to Deposit Ratio (FDR) variable on Non-Performing Financing (NPF).